2008
DOI: 10.1177/0011000007309489
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Heterosexism

Abstract: This article provides an integrated critical review of the literature on internalized heterosexism/internalized homophobia (IH), its measurement, and its psychosocial correlates. It describes the psychometric properties of six published measures used to operationalize the construct of IH. It also critically reviews empirical studies on correlates of IH in the areas of sexual identity formation and the coming-out process; mental, psychosocial, and physical health; substance use; sexual risk-taking behavior; int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(90 citation statements)
references
References 91 publications
8
82
0
Order By: Relevance
“…Researchers define the process by which lesbians and gay men learn, acknowledge, and accept the prevailing social biases against them as internalized heterosexism or internalized homophobia (Mildner 2001;Nungesser 1983;Shidlo 1994;Troiden 1989). Internalized homophobia is a multidimensional construct that includes negative feelings about oneself as gay or lesbian as well as negative perceptions about others' views of homosexuality (Ross and Rosser 1996;Szymanski et al 2008). Internalized homophobia therefore involves negative personal feelings about being gay or lesbian, negative attitudes (such as disrespect) directed at members of one's own group, the assumption that heterosexual people are superior in some way, and a weak connection to the gay and lesbian community at large.…”
Section: Gay and Lesbian Internalization Of Heterosexist Biasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers define the process by which lesbians and gay men learn, acknowledge, and accept the prevailing social biases against them as internalized heterosexism or internalized homophobia (Mildner 2001;Nungesser 1983;Shidlo 1994;Troiden 1989). Internalized homophobia is a multidimensional construct that includes negative feelings about oneself as gay or lesbian as well as negative perceptions about others' views of homosexuality (Ross and Rosser 1996;Szymanski et al 2008). Internalized homophobia therefore involves negative personal feelings about being gay or lesbian, negative attitudes (such as disrespect) directed at members of one's own group, the assumption that heterosexual people are superior in some way, and a weak connection to the gay and lesbian community at large.…”
Section: Gay and Lesbian Internalization Of Heterosexist Biasesmentioning
confidence: 99%
“…Stronger levels of internalized homophobia are associated with lower levels of self-esteem and increased levels of depression and psychological distress in lesbians and gay men (for a review, see Szymanski et al 2008). These findings parallel effects observed for members of other disadvantaged groups (e.g.…”
Section: Gay and Lesbian Internalization Of Heterosexist Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mustanski's (2010, 2011) meta-analytic reviews on the relationship between IH and mental health and between IH and sexual risk taking found largely small effect sizes for these associations. Recently, Szymanski and collaborators (Szymanski, Kashubeck-West, & Meyer, 2008a, 2008b examined the psychometric properties of instruments for measuring IH. They concluded that there were at least five measures with adequate reliability and validity support, but that more research was needed related to the measurement of IH, particularly with regard to racial and ethnic minority LGB individuals.…”
mentioning
confidence: 99%
“…For example, the literature base in areas related to homophobia/ heterosexism, etc., have been critiqued for use of measures that may not reflect the intended constructs and for using confusing and overlapping terminology (Smith et al 2012;Szymanski et al 2008b), and some of this controversy may result from fuzzy or unclear definitions of constructs. Relatedly, it is somewhat surprising that among their critiques of homophobia, McCormack and Anderson (2014) did not address the argument that homophobia is not a phobia and thus is overly and overtly pathologizing-an argument that would persist against the term homohysteria (Szymanski et al 2008a).…”
Section: Operational Definitionsmentioning
confidence: 99%